Longitudinal trends in blood pressure, prevalence, awareness, treatment, and control of hypertension in the Czech population. Are there any sex differences? - Cífková, Renata; Bruthans, Jan; Strilchuk, Larysa; Wohlfahrt, Peter; Krajčoviechová, Alena; Šulc, Pavel; Jozífová, Marie; Eremiášová, Lenka; Pudil, Jan; Linhart, Aleš; Widimský, Jiří; Filipovský, Jan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Hypertension is the most common cardiovascular disease which substantially increases cardiovascular morbidity and mortality. Despite the broad availability of antihypertensive medication, control of hypertension is not satisfactory worldwide. Objective The study aim was to assess longitudinal trends in blood pressure, prevalence, awareness, treatment, and control of hypertension in a representative population sample of the Czechia from 1985 to 2016/2017, focusing on sex differences. Methods A total of 7,606 men and 8,050 women aged 25–64 years were screened for major CV risk factors in seven independent cross-sectional surveys run consistently in the same six country districts of the Czechia between 1985 and 2016/2017. The population samples were randomly selected. Results Over a study period of 31/32 years, there was a significant decline in systolic and diastolic blood pressure in both sexes, whereas the prevalence of hypertension decreased only in women. There was an increase in hypertension awareness in both sexes over the entire study period with consistently higher rates in women. The proportion of individuals treated with antihypertensive drugs increased significantly in both sexes throughout the study, again with consistently higher rates in women. Control of hypertension increased significantly over the study period with consistently higher rates in women. The age-adjusted trends in blood pressure, prevalence, awareness, and treatment of hypertension were significantly different in men and women, always in favor of women. The age-adjusted trends in control of hypertension in treated patients were equally poor in both sexes. Conclusion There are significant differences in longitudinal trends in blood pressure, prevalence, awareness, treatment, and control of hypertension between men and women, always in favor of women except for the control of hypertension in treated patients, where it is equally poor in both sexes.